2003
DOI: 10.1101/gad.281503
|View full text |Cite
|
Sign up to set email alerts
|

Distinct HP1 and Su(var)3-9 complexes bind to sets of developmentally coexpressed genes depending on chromosomal location

Abstract: Heterochromatin proteins are thought to play key roles in chromatin structure and gene regulation, yet very few genes have been identified that are regulated by these proteins. We performed large-scale mapping and analysis of in vivo target loci of the proteins HP1, HP1c, and Su(var)3-9 in Drosophila Kc cells, which are of embryonic origin. For each protein, we identified ∼100-200 target genes among >6000 probed loci. We found that HP1 and Su(var)3-9 bind together to transposable elements and genes that are pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
191
0
2

Year Published

2004
2004
2011
2011

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 157 publications
(211 citation statements)
references
References 49 publications
18
191
0
2
Order By: Relevance
“…In fact, the Drosophila data suggests the formation of a static domain, perhaps through the use of insulators, that delimits the local effect on expression. A recent genomic analysis of HP1 and Su(var)3-9 binding supports a domain architecture of gene expression, as developmentally regulated genes display uniform patterns of association with one or both of the proteins (Greil et al 2003). Either by a spreading of modifications or the establishment of a domain, it is interesting that looping from CTs (as described above) appears to correlate with the range of effect seen at the genomic level (Ragoczy et al 2003).…”
Section: Genomic Organization Of Cellular Differentiation Genes and Devmentioning
confidence: 94%
“…In fact, the Drosophila data suggests the formation of a static domain, perhaps through the use of insulators, that delimits the local effect on expression. A recent genomic analysis of HP1 and Su(var)3-9 binding supports a domain architecture of gene expression, as developmentally regulated genes display uniform patterns of association with one or both of the proteins (Greil et al 2003). Either by a spreading of modifications or the establishment of a domain, it is interesting that looping from CTs (as described above) appears to correlate with the range of effect seen at the genomic level (Ragoczy et al 2003).…”
Section: Genomic Organization Of Cellular Differentiation Genes and Devmentioning
confidence: 94%
“…But many fruit fly genes have been found to inhabit pericentric heterochromatin at low density 40 , where they are expressed despite association with heterochromatin proteins 41 . The same appears to be true for Arabidopsis, in which one study mapped genes to a transposon-rich region thought at the time to be within centromeric DNA 20 .…”
Section: Discussionmentioning
confidence: 99%
“…This view has recently been challenged on several fronts with evidence of highly dynamic regulation and lively complex reassembly. For instance, recent data suggest important functions outside heterochromatin and point to Suv39-independent functions of HP1 members and vice versa (Greil et al 2003). Further more, photobleaching experiments using fluorochrome-tagged HP1 demonstrated that the majority of the HP1 proteins are highly mobile with rapid movements in and out of heterochromatin domains (Festenstein et al 2003;Schmiedeberg et al 2004).…”
Section: Stability and Dynamics Of Epigenetic Gene Regulationmentioning
confidence: 99%